HAKIKAT ASAS PENDIDIKAN SEPANJANG HAYAT - Abdul Wahab Syakhrani; Mahdia Azzahra, Siti Aulia Rahmah, Siti Rahma Daniati (CV. ADIBA AISHA AMIRA, 2025)
Lifelong education is a concept that emphasises that the educational process does not stop at a certain age but continues throughout a person's life. This concept places education as an integral part of self-development, encompassing formal and non-formal learning as well as continuous life experiences. Lifelong education is based on the principle that humans are a unity of living and dynamic potential, so education must provide space for lifelong learning to adapt to changes and the needs of the times. The role of lifelong education is very important in shaping an independent, adaptive, and productive learning society. Thus, lifelong education is the basis for comprehensive and sustainable education policies and the foundation for improving the quality of life of individuals and society.